Repeat revascularisation outcomes after percutaneous coronary intervention in patients with rheumatoid arthritis. Issue 5 (30th December 2015) - Sintek, Marc A; Sparrow, Christopher T; Mikuls, Ted R; Lindley, Kathryn J; Bach, Richard G; Kurz, Howard I; Novak, Eric; Singh, Jasvindar
Abstract : Objective: To investigate repeat revascularisation outcomes in patients with rheumatoid arthritis(RA) after percutaneous coronary intervention (PCI). Methods: We performed a single-centre, retrospective matched cohort study of patients with RA matched to non-RA patients post PCI. Primary endpoints were time to target lesion revascularisation (TLR) and target vessel revascularisation (TVR) analysed by Cox proportional hazard shared frailty models. Results: A total of 228 lesions (143 patients) were identified in the RA cohort and matched to 677 control lesions (541 patients). TLR occurred in 33% (n=75) of RA lesions versus 25% (n=166) of control lesions (adjusted HR 1.3; 95% CI 0.97 to 1.8). TVR occurred in 39% (n=89) of RA lesions versus 31% (n=213) of control lesions (adjusted HR 1.15; 95% CI 0.82 to 1.6). There was a significant hazard for TLR (adjusted HR 1.48; 95% CI 1.03 to 2.13) and TVR (adjusted HR 1.55; 95% CI 1.12 to 2.14) when excluding lesions with revascularisation events or follow-up less than 1 year. When stratified by treatment with methotrexate or tumour necrosis factor (TNF) α inhibitors or both at discharge, lesions from patients with RA treated with these agents had similar TVR and TLR as control lesions, whereas lesions from patients with RA not treated with these agents had significantly more TLR and TVR (TLR adjusted HR 1.48; 95% CI 1.08 to 2.03; TVR adjusted HR 1.38; 95% CI 1.04 to 1.84). Conclusions: RA predisposes to repeat revascularisation, specifically in patients followed after the 1-year landmark. In the absence of RA treatments including methotrexate and/or TNFα inhibitors, RA is associated with a 50% increased relative risk of repeat revascularisation following PCI. These findings emphasise the adverse effects of chronic inflammation on the durability of PCI and provide further support for aggressive anti-inflammatory treatment in patients with RA.